2008
DOI: 10.1159/000170381
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the Picryl Chloride-Induced Allergic Dermatitis Model in Mouse Ear Lobes by 12-<i>O</i>-Tetradecanoylphorbol 13-Acetate, and Analysis of the Role of Histamine in the Modified Model

Abstract: Background: In atopic dermatitis, inflammation induced by antigen-nonspecific stimuli further enhances the allergic inflammation. However, there is no experimental model in which allergic dermatitis is evoked where the inflammation has been induced by antigen-nonspecific stimuli. Here, we established a novel dermatitis model in mice and analyzed the role of histamine. Methods: After sensitization with picryl chloride (PiCl) by painting on ear lobes of cyclophosphamide-treated mice, 12-O-tetradecanoylphorbol 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
40
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 72 publications
7
40
0
Order By: Relevance
“…We found that this model showed features similar to those observed in atopic dermatitis: crust formation, epidermal hyperplasia, and a vigorous infiltration of leukocytes including eosinophils (12). Analysis of the time course changes in the PiCl-induced swelling showed that the allergic inflammation was shifted from a delayed-type response to a biphasic response consisting of a weak immediate-phase response and a late-phase response by painting with TPA (Fig.…”
Section: Introductionsupporting
confidence: 68%
See 4 more Smart Citations
“…We found that this model showed features similar to those observed in atopic dermatitis: crust formation, epidermal hyperplasia, and a vigorous infiltration of leukocytes including eosinophils (12). Analysis of the time course changes in the PiCl-induced swelling showed that the allergic inflammation was shifted from a delayed-type response to a biphasic response consisting of a weak immediate-phase response and a late-phase response by painting with TPA (Fig.…”
Section: Introductionsupporting
confidence: 68%
“…The application of TPA on days 5 and 10 decreased the level of IFN-γ mRNA, but increased that of IL-4 mRNA (Fig. 3, hatched columns), indicating that the application of TPA induced a shift in the cytokine milieu from a Th1-to a Th2-type profile (12). Thus, this model will be a suitable model for studying the mechanisms by which the antigennonspecific inflammation worsens allergic dermatitis.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations